2015
DOI: 10.11648/j.ijaas.20150104.12
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Interaction Effect Between Salinity and Growth Regulators on Salt Tolerance of Two Bread Wheat Cultivars

Abstract: Absract:The objective of this study is to investigate the effect of the interaction between salinity and plant growth regulators (Kinetin and gibberellin) on the salt tolerance of two bread wheat cultivars (Dijilla) and (Tamooze-2) under salinity conditions. The present study was conducted to assess the effects of Kinetin and gibberellin on plant dry matters (shoots and roots), chlorophyll content and stability in upper leaves, salt tolerance index, and organic contents in plant leaves of the two cultivars gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In the previous study, Al-Mishhadani et al (2) showed that the TaNIP gene found only in these selected genotypes with length of 189 bp, while this gene absent in salt sensitive cultivar (Iraq) and gave high gene expression at high salinity level (16 ds/m). Therefore, according to these results, these genotypes are considered as a high salt tolerant genotypes, which improved through plant breeding programs genotypes, this conclusion is agreed with the previous studies, which they reported that there is a strong development in salt tolerance obtained in these selected genotypes through plant breeding program (2,5,7,8). Under high salinity condition, the selected genotypes were more salt tolerance than the local cultivars, may be due to they contained high organic compounds in their upper leaves (Table 2).…”
Section: Organic Compoundsupporting
confidence: 89%
See 1 more Smart Citation
“…In the previous study, Al-Mishhadani et al (2) showed that the TaNIP gene found only in these selected genotypes with length of 189 bp, while this gene absent in salt sensitive cultivar (Iraq) and gave high gene expression at high salinity level (16 ds/m). Therefore, according to these results, these genotypes are considered as a high salt tolerant genotypes, which improved through plant breeding programs genotypes, this conclusion is agreed with the previous studies, which they reported that there is a strong development in salt tolerance obtained in these selected genotypes through plant breeding program (2,5,7,8). Under high salinity condition, the selected genotypes were more salt tolerance than the local cultivars, may be due to they contained high organic compounds in their upper leaves (Table 2).…”
Section: Organic Compoundsupporting
confidence: 89%
“…Increasing salt tolerance in plant requires new genetic source of this character powerful and molecular techniques for detecting salt tolerance genes in new material useful for determining the salt tolerance degree. Salt tolerance in plant depends on physiological mechanisms controlled by genes which gave expression under salinity conditions (2,5). Plants have evolved several salt tolerance mechanisms to reduce the adverse effect of salinity (16), this mean that there are different genes for controlling these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the genetic improvement or advance for salt tolerance is realized through plant breeding programs. The same genetic improvement was realized in the selected cultivar (Dijilla) through this program [20].…”
Section: Discussionmentioning
confidence: 81%